Dynamics of a new seismic isolation device based on tribological smooth rocking (TROCKSISD). (15th August 2019) - Froli, Maurizio; Giresini, Linda; Laccone, Francesco
Highlights: A novel concept of isolation device for slender structures or historic assets based on smooth rocking and friction is introduced and discussed. The re-centering capacity is enhanced by means of viscous-elastic dampers and of properly distributed springs. Equations of motion are provided for the corresponding 2DOFs simplified system. Performance-based design procedures are suggested for adequately designing the isolation device. Abstract: A novel isolation device is introduced to seismically protect slender structures or historic assets within the philosophy of Damage Avoidance Design (DAD). This device is conceived to allow smooth, controlled and damped rocking thanks to spherical contact surfaces, elastic springs which ensure re-centering, frictional layers and viscous elastic dampers able to dissipate energy during motion. The conceptual framework of the device is analyzed, and corresponding equations of motions obtained for the equivalent two degrees-of-freedom system. The proposed Performance Based Approach allows identifying geometric and mechanical features of the system. Extensive dynamic analyses with spectra-compatible ground motions are performed and the primary contribution of friction, developed by the relative slip of the two spherical surfaces, is discussed. Finally, the dynamic response under selected earthquakes is evaluated by comparing the isolated and the corresponding not isolated response, to highlight the beneficial effects produced by the proposed isolation technique.